Kemampuan Mitigasi Cyberbullying terhadap Resiliensi Remaja - Syifa’ul Husna; Audyna Navisa; Alifa Amalia; Dinda Setiya; Shofi Afra; Sambodo Sriadi Pinilih (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Cyberbullying is a term known in the world of bullying involving technology which uses the internet. Mitigation is reduction, prevention or can be said to be the process of seeking various preventive actions to minimize the negative impact of disasters that will occur. Resilience has to do with how individuals overcome difficulties and unpleasant conditions in their lives. Adolescence is a transition period from childhood to adulthood. It turns out that there are still many who think that cyberbullying is normal. Objective: The phenomenon of problems, efforts that have been implemented, weaknesses or shortcomings of efforts, and solutions to solving cyberbullying problems that occur in Indonesia. Methods: This review uses a method containing reviews, summaries, and thoughts of the author from several literature sources (articles, journals, books, information) on the topic discussed. Preparation of this article through google scholar. The result of this paper is a literature review of the research. Results: The results of this literature study prove that it is important to prevent cyberbullying to adolescents. One way is through the provision of health education, pre test and post test. The goal is that adolescents know about what cyberbullying is from understanding, types, impacts, and prevention of cyberbullying.